2012
DOI: 10.1111/j.1464-410x.2012.11392.x
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic acid in combination with serine/threonine phosphatase inhibitors induces enhanced cytotoxicity and apoptosis in hormone‐refractory prostate cancer cell lines by decreasing the activities of PP1 and PP2A

Abstract: E 11 4 7 OBJECTIVES• To investigate if the cytotoxic and apoptotic effect of zoledronic acid (ZA) can be enhanced by the addition of the serine/threonine protein phosphatase inhibitors calyculin A (CA) and okadaic acid (OA) in hormone and drug refractory prostate cancer cells, PC-3 and DU-145.• To discover the effect of these combination treatments on phosphatase 1 (PP1) and PP2A protein expression levels in prostate cancer cells. MATERIALS AND METHODS• An XTT cell viability assay was used to determine cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…However, PP2A inhibitors have also shown benefit for cancer treatment in certain conditions. For instance, PP2A inhibition has been shown to induce apoptosis in T leukemia cells, pancreatic cancer, and prostate cancer (11,(40)(41)(42), and gene therapy strategy targeting PP2A has shown efficacy on HCC in vitro and in vivo (43). In addition, endothall, another PP2A inhibitor, even showed that growth inhibition preferentially inhibited HCC cell lines compared with normal fetal hepatocytes (44).…”
Section: Discussionmentioning
confidence: 99%
“…However, PP2A inhibitors have also shown benefit for cancer treatment in certain conditions. For instance, PP2A inhibition has been shown to induce apoptosis in T leukemia cells, pancreatic cancer, and prostate cancer (11,(40)(41)(42), and gene therapy strategy targeting PP2A has shown efficacy on HCC in vitro and in vivo (43). In addition, endothall, another PP2A inhibitor, even showed that growth inhibition preferentially inhibited HCC cell lines compared with normal fetal hepatocytes (44).…”
Section: Discussionmentioning
confidence: 99%
“…The reason, why the delay of SREs does not results in improved survival, is unclear. A couple of preclinical studies have shown direct anticancer effects of bisphosphonates on PC cells [ 37 ] and indicate an important role of the mevalonate pathway in the biology of PC [ 38 ]. Moreover, studies showing that the mortality of men with hip fractures is as high as 38% within one year after fracture raise expectations that SRE prevention may result in improved survival [ 39 ].…”
Section: Bone Targeted Therapies For Prevention Of Skeletal Relatementioning
confidence: 99%
“…Moreover, the endogenous protein Cancer Inhibitor of PP2A (CIP2A) has been reported to be highly expressed and involved in PCa progression via c-MYC regulation [ 9 , 10 ], and CIP2A knockdown is able to resensitize metastatic castration-resistant PCa cells to cabazitaxel [ 11 ]. However, contradictory results about the potential therapeutic value of PP2A activation in PCa have been reported to date [ 12 , 13 , 14 , 15 , 16 ]. Whereas some studies support the antitumor properties derived from PP2A activation of compounds such as sodium selenate, ceramide, or carnosic acid [ 12 , 13 , 14 ], others highlight that PP2A inhibition led to anticancer effects [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%